Characterization, and Functional Analysis of Hsp70 and Hsp90 Gene Families in Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) - Ding, Jian-hao; Zheng, Lu-xin; Chu, Jie; Liang, Xin-hao; Wang, Jun; Gao, Xiao-wen; Wu, Fu-an; Sheng, Sheng (Frontiers in Physiology, 2021)
Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) is a destructive mulberry pest, causing great damage to mulberry in China. Heat shock proteins (Hsps) are involved in various signal pathways and regulate lots of physiological processes in insects. The function of Hsps in G. pyloalis, however, has still received less attention. Here, we identified five Hsp genes from G. pyloalis transcriptome dataset including two Hsp70 family genes (GpHsp71.3 and GpHsp74.9) and three Hsp90 family genes (GpHsp82.4, GpHsp89, and GpHsp93.4). Quantitative Real-time PCR validation revealed that all Hsps of G. pyloalis have significant expression in pupal and diapause stage, at which the larvae arrest the development. Expressions of GpHsp71.3 and GpHsp82.4 were increased significantly after thermal treatment at 40°C, and this upregulation depended on heat treatment duration. Furthermore, silencing GpHsp82.4 by RNA interference led to a significant increase in mortality of G. pyloalis larvae under the heat stress compared to the control group. After starvation stress, the expression levels of GpHsp82.4 and GpHsp93.4 were significantly increased. At last, after being parasitized by the parasitoid wasp Aulacocentrum confusum, Hsp70 and Hsp90 genes of G. pyloalis were decreased significantly in the early stage of parasitization and this moderation was affected by time post-parasitization. This study highlights the function of G. pyloalis Hsps in response to environmental stress and provides a perspective for the control of this pest.